The Effectiveness of Cognitive Rehabilitation in Improving Working Memory and Attention in Acute COVID-19 Survivors - Noroozi Fashkhami, Moein; Pour Mohammadi, Somayeh; Azadyekta, Mehrnaz (Shahroud Journal of Medical Sciences, 2024)
Background: This study aimed to determine the effectiveness of cognitive rehabilitation in improving working memory and attention in acute COVID-19 survivors.Methods: The current study utilized a quasi-experimental design with a Pre-test Post-test, and a control group. The target population consisted of all individuals suffering from acute COVID-19 in the city of Tehran. From this target population, 36 individuals were selected using purposive sampling. These 36 individuals were randomly assigned to two groups of 18, experimental and control. Assessments were conducted on the participants before and after the intervention. The experimental group received the RehaCom cognitive rehabilitation, while the control group did not receive any intervention. The data collection instruments were tests of working memory, selective attention, and divided attention from the RehaCom cognitive rehabilitation software. Data analysis was done using multivariate analysis of covariance (MANCOVA) and univariate analysis of covariance (ANCOVA) with SPSS26 software. The significant level was set at 0.05.Results: The findings showed that there was no significant difference in working memory between the experimental and control groups (P-value<0.05). Additionally, no significant difference was observed in the subscales of reaction speed and visual divided attention between the experimental and control groups. However, there was a significant difference in the subscales of auditory divided attention and reaction control between the experimental and control groups (P-value<0.05).Conclusions: Considering the means of research variables in the Post-test stage, it can be concluded that cognitive rehabilitation can improve reaction control and auditory divided attention in acute COVID-19 survivors.